2013
DOI: 10.1016/j.ccr.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Is Required for Germinal Center Formation and Somatic EZH2 Mutations Promote Lymphoid Transformation

Abstract: The EZH2 histone methyltransferase is highly expressed in germinal center (GC) B-cells and targeted by somatic mutations in B-cell lymphomas. Here we find that EZH2 deletion or pharmacologic inhibition suppresses GC formation and functions in mice. EZH2 represses proliferation checkpoint genes and helps establish bivalent chromatin domains at key regulatory loci to transiently suppress GC B-cell differentiation. Somatic mutations reinforce these physiological effects through enhanced silencing of EZH2 targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
836
5
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(909 citation statements)
references
References 39 publications
41
836
5
7
Order By: Relevance
“…Previous studies have shown that Ezh2 is required for GC formation and the SWI/SNF complex synergistically regulates several genes together with the Ezh2-PRC2 complex (36)(37)(38)(39). MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Ezh2 is required for GC formation and the SWI/SNF complex synergistically regulates several genes together with the Ezh2-PRC2 complex (36)(37)(38)(39). MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40).…”
Section: Discussionmentioning
confidence: 99%
“…The biology is therefore complex, and depending on the tissue and the underlying genetic landscape of the cell, the chromatin--associated protein could act as an oncogene in one setting but be a tumour suppressor in other circumstances. This is for instance illustrated by EZH2, in which gain--of--function mutations promote lymphoid transformation 16,33,37,79 , and loss--of--function mutations promote MDS and T--ALL 36,80--83 .…”
Section: Discussionmentioning
confidence: 99%
“…83 EZH2 has been described as an essential regulator for B cell activation and is involved in germinal center-derived neoplasms. 84 In myeloid neoplasia, EZH2 is most often affected by mutations leading to direct abrogation of histone methyltransferase activity, suggesting that EZH2 acts as a tumor suppressor for myeloid malignancies. 79 There is evidence for both increased and decreased activity of enzymes controlling H3K27 methylation in other cancers, 76,85 supporting the idea that a precise balance of this methylation is critical for normal cell growth and for a context-dependent role of polycomb proteins in oncogenesis.…”
Section: Kmts and Prmtsmentioning
confidence: 99%